Studies on Production of Valuable Aromatics Benzene, Toluene and Ethylbenzene Using Multiphase Catalytic Pyrolysis of Waste Expanded Polystyrene - Verma, Anjali (IIT BHU Varanasi, 2022)
Abstract is available in the content
Keywords: Studies on Production of Valuable Aromatics Benzene; Toluene and Ethylbenzene Using Multiphase Catalytic; Pyrolysis of Waste Expanded Polystyrene